Associated Factors to Uptake of Human Papiloma Virus Vaccine 2 Among Girls of Ages 9-14 Years in Igombe Sub-County Bugweri District. - Olinga, Micheal Albert; Nabaggala, Grace; Carol, Karen (Student's Journal of Health Research Africa, 2021)
Background: Human papillomavirus (HPV) infection is a sexually transmitted infection and it’s estimated that 75% of sexually active people are infected with HPV during their lifetime, HPV vaccines are being marketed in many countries throughout the world, and are highly efficacious in preventing 90% of infections due to HPV virus. Even though HPV vaccination is recommended and mostly carried out in schools, there are multiple challenges in implementing and increasing the vaccine's uptake. Methodology: The study employed a cross-sectional design and utilized a sample size of 424 respondents. Sampling was done by systemic random sampling and data was collected using a self-administered questionnaire. Thereafter, data analysis was done using SPSS version 1.8. Results: The majority of respondents 77 (50.7%) did not receive HPV2 due to fear of needle prick pain, 51 (33.6%) due to discouragement by guardians, while minority 24 (15.8%) of the respondents were not given an appointment date. 127 (30%) of the respondents reported that previous experience such as painful needle pricks, other side effects such as headaches and fevers would hinder HPV2 reception. Recommendations: The government of Uganda through the Ministry of Health should ensure that there are national sensitization programs targeted at improving the uptake of HPV vaccines among girls aged 9-14 years both those at schools and those out of schools. Conclusion: There was poor uptake of HPV2 vaccine among girls aged 9-14 years in Igombe sub-county, this was mainly attributed to poor support by the parents/guardians to their girl children towards the vaccine, failure of health workers to issue return dates to the girls, distant health centers and fear of needle pricks and other side effects such as headaches and fevers. Sensitization of the communities and continuous medical education for the health workers is highly recommended to improve the utilization of the vaccine.